STUDY OF PHOSPHORS ZnS:Mn,Cl PHOTOLUMINESCENCE UNDER DYNAMICAL PHOTOEXCITATION - Leonid Mikhnev; Evgheny Bondarenko; Dmitry Valyukhov; Alexey Skomorokhov; Oleg Chapura; Askhat Ilyasov; Mihail Annenko; Anna Sbitneva (Вестник Северо-Кавказского федерального университета)
Photoluminescence excitation of ZnS:Mn,Cl with different activator concentration was study using static and dynamical photoexcitation regimes. We determined that concentration of manganese and regime of photoexcitation has a great influence on form of photoluminescence excitation spectra. Luminescence kinetic curves of ZnS:Mn,Clphosphorous with 1,1 wt % manganese were measured. We basing on analysis of dependence ofphotoluminescence from concentration of manganese and influence of regimes ofphotoexcitation have offered potential mechanism of transmission energy to manganese ions in ZnS:Mn,Cl.